Mathematics Question and Solution

By Ogheneovo Daniel Ephivbotor
2nd November, 2023

sinxcos60+sin60cosx-(cosxcos45+sinxsin45) = 0


0.5sinx+½(√(3)cosx)-½(√(2)cosx)-½(√(2)sinx) = 0


0.5sinx-½(√(2)sinx) = ½(√(2)cosx)-½(√(3)cosx)


sinx(1-√(2)) = cosx(√(2)-√(3))


sinx = ((√(2)-√(3))cosx)/(1-√(2))


sinx = ((√(2)+2-√(3)-√(6))cosx)/-1


sinx = -(√(2)+2-√(3)-√(6))cosx


sinx = (√(3)+√(6)-√(2)-2)cosx


(sinx/cosx) = (√(3)+√(6)-√(2)-2)


tanx = (√(3)+√(6)-√(2)-2)


x = atan(√(3)+√(6)-√(2)-2))


x = 37.5°


It implies;


sinx = (√(3)+√(6)-√(2)-2)cos(37.5)


sinx = (√(3)+√(6)-√(2)-2)cos(½(75))


sinx = 0.608761429 exactly in decimal.

Tags:

WhatsApp Google Map

Safety and Abuse Reporting

Thanks for being awesome!

We appreciate you contacting us. Our support will get back in touch with you soon!

Have a great day!

Are you sure you want to report abuse against this website?

Please note that your query will be processed only if we find it relevant. Rest all requests will be ignored. If you need help with the website, please login to your dashboard and connect to support